Identifying and analyzing logistics land use: : A case study of the Rhineland Metropolitan Region - Thiemermann, Andre; Groß, Florian (REGION, 2025)
In Germany, the identification of logistics land is rarely done, among other things due to the anonymization of employment and building data. The paper at hand gives an overview of data sources used for the identification of spatial patterns of logistics facilities and presents a method for identifying logistics land based on publicly available data, to present an image of the existing spatial structure of logistics land. Identified spatial hotspots are mostly located in Metropolises/Regiopolises and their suburbs, along highways in areas with flat relief, and in the vicinity of large inland terminals/inland harbors.